The Implementation of Literacy through Positive Habits as an Effort to Strengthen Character in Elementary Schools - Jumiati (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
Strengthening student character is an important issue in education currently. This study aims to analyze the extent to which the implementation of literacy through positive habits can contribute the character strengthening. Through this case study method, it finds that students had a weak interest in reading. So that literacy activities emerged 15 minutes before learning begin. The obstacles face is the lack of interest in reading among students and the teacher involvement in the habituation process. The results of this study indicate that literacy through positive habits has great potential in students' character strengthening and it requires support from several factors, such as teachers, parental support, availability of reading materials, or a conducive school environment.